The Use of Kōans for Insight Evaluation Approach Training - Craig Russon; Karen Russon (The Evaluation Center at Western Michigan University, 2010)
Background: Since publishing a trilogy of articles relating Eastern mysticism to evaluation, the authors have received many inquiries about training.   Purpose: The article explains one promising new method under development-adapting the Zen practice of kōans for evaluation training.   Setting: Not applicable.   Subjects: Not applicable.   Research Design: Not applicable. Data Collection and Analysis: Not applicable.   Findings: Not applicable.   Conclusions: The authors believe that kōans can be used as a poetic technology for recalibrating evaluation practioners' attitudes and actions about evaluation.   Keywords: Insight evaluation approach, Eastern mysticism, kōans, training, Zen, enlightenment